Advanced Numerical Simulation and Modeling of Multi-Pass Welding Processes: Detailed Analysis of Temperature Distribution in Structural Elements - Dániel Gosztola; Peter Grubits; János Szép; Majid Movahedi Rad (Chemical Engineering Transactions)
The growing importance of numerical simulations in the welding industry stems from their ability to enhance structural performance and sustainability by ensuring optimal manufacturing conditions. The use of the finite element method (FEM) allows for detailed and precise calculations of the mechanical and material changes caused by the welding process. Acquiring knowledge of these parameters not only serves to augment the quality of the manufacturing process but also yields consequential benefits, such as reducing adverse effects. Consequently, the enhancement of structural performance and prolonged lifespan becomes achievable, aligning with overarching sustainability goals. To achieve this goal, this paper utilizes numerical simulations of welding processes based on experimental tests, with a specific focus on analyzing temperatures generated within the structures. In the finite element analysis (FEA), a total of 12 welding cycles were systematically modeled to align with experimental conditions, incorporating cooling intervals, preheating considerations, and the relevant section of the connecting concrete structure with studs. The outcomes of this research exemplify the potential of numerical simulation in the welding industry, demonstrating a diverse range of results achieved through FEA to enhance the quality of structures within the context of sustainability.